IoT enabled Smart Lighting System using STM32 microcontroller with high performance ARM® Cortex®-M3 core - Wu, Siyu; Abdulghani, Amir M.; Ansari, Shuja; Imran, Muhammad Ali; Abbasi, Qammer H. (2020 International Conference on UK-China Emerging Technologies (UCET), 2020)
Green technology for economically viable engineering designs and sustainable environment is highly desirable for future smart city applications. An intelligent system for operating and controlling lighting in order to save energy is developed and presented in this article. The system is implemented on Alibaba Cloud IoT platform on STM32 development board using STM32 medium-density performing microcontroller with high performance ARM ® Cortex ® -M3 RISC core. It includes communication between wireless sensors and actuators, and control of light sources. The HC-SR501 human infrared sensor is also used for detecting people and BH170 photosensitive sensor for synthetic brightness detection. The system includes indicators to represent three orders of magnitude of temperature sensor reading. The system developed in this work also features (i) an OLED display unit enabling users to view sensed data easily and (ii) Web platform-based User Interface (dashboard) for allowing users to easily interact with the system. The overall system provides a practical and interactive solution for data visualization and to remotely control light sources.